Business ethics: principles and practices - Albuquerque, Daniel . (Oxford University Press, 2010)
Starting with a broad overview of the meaning and scope of ethics and the development of ethical thought, the book puts forward the applications of ethical standards to business areas such as corporate governance, marketing and brand management, advertising, and finance. The discussion shifts to a more human level with the various issues of the workplace ethics as well as consumer rights. Special focus is given to ethical choices related to the environment, cyber space and criminal intimidation. Contemporary issues like corporate code of ethics, political correctness and the role played by NPO and NGO in upholding moral values are discussed in detail. Finally, several open-ended issues like Intellectual Property.